Issues concerning the statutory duties of licensed housing developers under section 7 of the Housing Development (Control & Licensing) Act 1966 (Act 118) in Peninsular Malaysia - Md Dahlan, Nuarrual Hilal (2015)
In Peninsular Malaysia, private housing developers who carry out housing development are subject to the Housing Development (Control & Licensing) Act 1966 (Act 118).Parliament enacted Act 118 for the purpose of protecting the rights of the purchasers.In addition, the current aims of Act 11 8, as enshrined in the preamble and the long title of Act 11 8, is to provide for the control and licensing of the business of housing development in.Peninsular Malaysia, the protection of the interest of purchasers and for matters connected therewith.In Rasiah Munusamy v. Lirn Tan & Sons Sdn. Bhd [I9851 2 MLJ 291(Supreme Court) the appellant purchaser alleged that the respondent vendor orally agreed to sell and transfer to the appellant a double storey terrace house which the respondent vendor undertook to build.The respondent vendor alleged that the oral agreement was not valid under rule 12(1) of the Housing Developers Rules, 1970.The learned trial judge in the High Court held that since only the method or mode of entering into the agreement was in contravention of the law, the verbal agreement was valid and enforceable. Likewise, the Supreme Court, in relation to the enforceability of the oral agreement, held, inter alia, that, although the oral agreement did not comply with the provision of rule 12(1) of the Housing Developers (Control and Licensing) Rules, 1970, the appellant purchaser clearly belongs to a class for whose protection the statutory prohibition is imposed and as such the appellant can enforce his right for specific performance of the oral contract of sale provided he is a bonafide purchaser. Secondly, the Supreme Court opined, in the circumstances of this case, the appellant purchaser could not be said to be a rnalafide purchaser. He cannot be deprived of the protection given by the Housing Developers legislation nor is there justification in holding that the appellant purchaser had used the housing developers' legislation as an engine of fraud.The appellant purchaser has not perpetrated any fraud, legal or equitable, and his claim for specific performance should have been granted. Mohamed Azmi SCJ in this case said at pages 294-295: